Death Concerns, Benefit-Finding, and Well-Being During the COVID-19 Pandemic - Cox, Cathy R.; Swets, Julie A.; Gully, Brian; Xiao, Jieming; Yraguen, Malia (Frontiers in Psychology, 2021)
Because of the coronavirus (COVID-19) pandemic, reminders of death are particularly salient. Although much terror management theory research demonstrates that people engage in defensive tactics to manage mortality awareness, other work shows that existential concerns can motivate growth-orientated actions to improve health. The present study explored the associative link between coronavirus anxieties, fear of death, and participants’ well-being. Results, using structural equation modeling, found that increased mortality concerns stemming from COVID-19 were associated with heightened benefit finding (e.g., relationship investment, gratefulness, patience) from the pandemic. Increased benefit finding, in turn, was related to higher life satisfaction, meaning in life, self-esteem, resilience, and vitality while also correlating negatively with depression and stress scores. There was no evidence for reverse mediation in that fear of mortality did not predict well-being through coronavirus worries. Overall, although many persons have experienced mental health concerns (e.g., fear, stress) as a function of the COVID-19 pandemic, our findings demonstrate positive benefits that paradoxically follow in terms of an increased appreciation of life, improved relationships, and better health.